2016
DOI: 10.3892/mmr.2016.5636
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of CD44 is associated with the occurrence and migration of non-small cell lung cancer

Abstract: Non-small cell lung cancer (NSCLC) is a potentially fatal disease and the incidence is increasing annually. In order to diagnose and treat NSCLC effectively, greater understanding of its molecular mechanism is required. In the present study, 36 NSCLC tissues and 10 normal tissues were selected. Reverse transcription-quantitative polymerase chain reaction (RT-qPCR) was used to analyze the CD44 mRNA expression level in NSCLC tissue and DNA sequencing was performed to further verify the CD44 expression level. Dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 61 publications
0
25
0
Order By: Relevance
“…Previous studies have shown that CD44 genetic polymorphisms are closely associated with NSCLC genesis, bone metastasis, and TNM stage [13,14]. Independently of the TNM stage, CD44 genetic polymorphisms are predictive of a poor prognosis in postoperative NSCLC patients, especially in those with lung adenocarcinoma [15].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that CD44 genetic polymorphisms are closely associated with NSCLC genesis, bone metastasis, and TNM stage [13,14]. Independently of the TNM stage, CD44 genetic polymorphisms are predictive of a poor prognosis in postoperative NSCLC patients, especially in those with lung adenocarcinoma [15].…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, these macromolecules can modify their conformation, as a response to a change of environmental conditions (i.e. pH), thus acting as a stimuli-responsive system [38,39]. In general, the external functionalization affects MSNs biocompatibility, biodistribution, pharmacokinetics, particle stability, circulation time, tumor accumulation, cellular uptake, and therapeutic efficacy [32,40,41].…”
Section: Introductionmentioning
confidence: 99%
“…be overexpressed in NSCLC and involved in the occurrence and migration of NSCLC [5]. The genes L1TD1 (LINE-1 Type Transposase Domain Containing 1) and SPAG6 (Sperm Associated Antigen 6) are tumor-specifically methylated in NSCLC [6].…”
mentioning
confidence: 99%